Analysis of the factors influencing prolongation of inter-repair terms of capital repairs of the apartment house. Issue 1 (March 2020) - Korol, O A; Dekhtyar, E V
Abstract: In modern conditions, the most important method of ensuring the safety of the housing stock and improving the living conditions of the population is capital repairs, as a form of simple reproduction of the housing stock, inextricably interrelated with the process of expanded reproduction (construction, reconstruction and modernization). However, at the present time, despite the long, protracted process of reforming the housing and communal sector and a number of significant transformations and changes, the housing problem remains still unresolved. At the same time, it is impossible not to recognize the fact that the unsatisfactory state of the housing stock significantly reduces the level of socio-economic development of our country and the comfort of living of citizens. The article identifies the main factors that affect the prolongation of the inter-repair terms of capital repairs of an apartment building, and the ranking of ranks was made because of expert assessments. The vector of priorities for drawing up a curve of indicators of importance of estimated criteria is calculated.